The Pandemic Hits Us Hard, but We Don’t Lose Hope - Krisna Yuarno Phatama; Sholahuddin Rhatomy, MD; Asep Santoso; Nicolaas C. Budhiparama (Indonesian Hip and Knee Society (IHKS), 2021)
At the end of 2019, we faced a new variant of the coronavirus that can cause pneumonia and acute respiratory distress syndrome-like symptoms. It started in Wuhan, Hubei Province, China, and spread quickly to the whole world.This new virus is called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and can manifest as a disease called coronavirus disease 2019 (COVID-19). On March 13th, 2020 World Health Organization (WHO) declared COVID-19 as a global pandemic, and the story of frightening pandemic begin.